Out‐of‐hospital traumatic cardiac arrest: an underrecognized source of organ donors. (24th October 2013) - Faucher, Anna; Savary, Dominique; Jund, Jérôme; Dorez, Didier; Debaty, Guillaume; Gaillard, Arnaud; Atchabahian, Arthur; Tazarourte, Karim
Summary Whereas the gap between organ supply and demand remains a worldwide concern, resuscitation of out‐of‐hospital traumatic cardiac arrest (TCA) remains controversial. The aim of this study is to evaluate, in a prehospital medical care system, the number of organs transplanted from victims of out‐of‐hospital TCA. This is a descriptive study. Victims of TCA are collected in the out‐of‐hospital cardiac arrest registry of the French North Alpine Emergency Network from 2004 to 2008. In addition to the rates of admission and survival, brain‐dead patients and the organ transplanted are described. Among the 540 resuscitated patients with suspected TCA, 79 were admitted to a hospital, 15 were discharged alive from the hospital, and 22 developed brain death. Nine of these became eventually organ donors, with 31 organs transplanted, all functional after 1 year. Out‐of‐hospital TCA should be resuscitated just as medical CA. With a steady prevalence in our network, 19% of admitted TCA survived to discharge, and 11% became organ donors. It is essential to raise awareness among rescue teams that out‐of‐hospital TCA are an organ source to consider seriously.